THE CORRELATION OF MOBILITY TREND AND SITUATION OF COVID-19 BY COUNTRY, TERRITORY, AND AREA - Adrina Esther Liaw; Jihan Natra Shafira; Muhammad Aziz; Iche Andriyani Liberty (JURNAL KEDOKTERAN DAN KESEHATAN, 2021)
Each country around the world has taken several approaches in order to stop the spreading of the virus. This study was conducted to correlate the mobility trend and the situation of COVID-19 by country, territory, and area. This research paper adopts an observational analytic study with a cross-sectional approach for 115 countries from February 17th to August 27th, 2020. Tajikistan (r=0,956) and Italy (r=0,931) has the highest positive correlation for retail and recreations. For grocery,the highest degree of positive correlation is Mongolia (r=0,945) and Tajikistan (r=0,933). Bostwana and Italy showed highest significant positive correlation among countries (r=0,985 and r=0,902, respectively) for transit stations and residential  (r=0,994 and r=0,984). Bostwana also has the highest significant positive correlation for the park (r=0.980). Meanwhile, for the workplace, Mauritius (r=0,863) and Dominica (r=0,785) are countries with the highest degree of positive correlation with a cumulative case of COVID-19. Society's behavior plays an important role by following the government policy in order to slow down the spread of the virus. Retail and recreations, groceries and pharmacy stores, transit stations, parks, and workplaces found to have a significant positive correlation while residential have a significant negative correlation with cumulative cases of COVID-19 in most countries.